Detection of Intracellular Cytokines by Flow Cytometry. (3rd August 2015) - Yin, Yuzhi; Mitson‐Salazar, Alyssa; Prussin, Calman
Abstract: Intracellular cytokine staining (ICCS), employing fluorescently labeled MAbs detected by flow cytometry, has emerged as the premier technique for studying cytokine expression at the single‐cell level. Advances in polychromatic flow cytometry have dramatically enhanced the sophistication of ICCS investigations. ICCS can simultaneously measure multiple cytokines within a single cell, allowing the detection of complex cytokine phenotypes. Additionally, cytokines can be measured with a variety of other analytes, including transcription factors, proliferation dilution dyes, activation markers, and viability dyes. This capability, combined with the high throughput inherent in the instrumentation, gives ICCS an enormous advantage over other single‐cell techniques such as ELISPOT, limiting dilution, and T cell cloning. The unit describes intracellular staining of cells that have already been stimulated in vitro and fixed. Methods for in vitro activation by PMA and ionomycin or antigens, fixation of cell suspensions, and cell surface staining are also described. © 2015 by John Wiley & Sons, Inc.